The assessment of cholinesterase from the liver of Puntius javanicus as detection of metal ions - Sabullah M.K.; Sulaiman M.R.; Shukor M.Y.A.; Syed M.A.; Shamaan N.A.; Khalid A.; Ahmad S.A. (Hindawi Publishing Corporation, 2024)
Indexed by Scopus